Exercise training increases myocardial inotropic response in food restricted rats - Sugizaki, Mario Mateus; Dal Pai-Silva, Mach; Carvalho, Robson Francisco; Padovani, Carlos Roberto [UNESP]; Bruno, Alessandro; Nascimento, Andre Ferreira; Aragon, Flavio Ferrari; Barbosa Novelli, Ethel Lourenzi; Cicogna, Antonio Carlos [UNESP] (Elsevier B.V., 2006)
This study evaluated the effects of exercise training on myocardial function and ultrastructure of rats submitted to different levels of food restriction (FR). Male Wistar-Kyoto rats, 60 days old, were submitted to free access to food, light FR (20%), severe FR (50%) and/or to swimming training (one hour per day with 5% of load, five days per week for 90 days). Myocardial function was evaluated by left ventricular papillary muscle under basal condition (calcium 1.25 mM), and after extracellular calcium elevation to 5.2 mM and isoproterenol (I PM) addition. The ultrastructure of the myocardium was examined in the papillary muscle. The training effectiveness was verified by improvement of myocardial metabolic enzyme activities. Both 20% and 50% food restriction protocols presented minor body and ventricular weights gain. The 20%-FR, in sedentary or trained rats, did not alter myocardial function or ultrastructure. The 50%-FR, in sedentary rats, caused myocardial dysfunction under basal condition, decreased response to inotropic stimulation, and promoted myocardial ultrastructural damage. The 50%-FR, in exercised rats, increased myocardial dysfunction under basal condition but increased response to inotropic stimulation although there was myocardial ultrastructural damage. In conclusion, the exercise training in severe restriction caused marked myocardial dysfunction at basal condition but increased myocardial response to inotropic stimulation. (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: diet; training; myocardial function; inotropic stimulation; ultrastructure